2023
DOI: 10.1101/2023.01.13.523963
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global patterns of plant form and function are strongly determined by evolutionary relationships

Abstract: Plants display an incredible variety of forms and functions, which sustains a vast diversity of ecosystems on Earth. This diversity is the result of two forces: environmental filtering, the selection of phenotypes fit to a specific habitat; and evolutionary history, genetic constraints that determine the potential adaptations that species may evolve. To date, most studies have focused on describing macroecological patterns of trait variation, while the role of evolutionary history in determining these patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…A relatively low phylogenetic signal for LMA agrees with a global analysis (Flores et al, 2014), while it is known that LA usually carries a relatively high phylogenetic signal (Moles et al, 2005). Similarly, Capdevila et al (2023) found that the size-related dimension of the global spectrum of plant form and function carries a higher phylogenetic signal than the leaf economic dimension. Although correlative, our results suggest that the relative importance of ITV might be greater for those traits that are primarily shaped by environmental filtering (economic traits) compared to those traits that are primarily determined by the evolutionary history of the species (size-related traits).…”
Section: Effect Of Itv On the Variance Explained Along The Trait Spac...supporting
confidence: 68%
See 1 more Smart Citation
“…A relatively low phylogenetic signal for LMA agrees with a global analysis (Flores et al, 2014), while it is known that LA usually carries a relatively high phylogenetic signal (Moles et al, 2005). Similarly, Capdevila et al (2023) found that the size-related dimension of the global spectrum of plant form and function carries a higher phylogenetic signal than the leaf economic dimension. Although correlative, our results suggest that the relative importance of ITV might be greater for those traits that are primarily shaped by environmental filtering (economic traits) compared to those traits that are primarily determined by the evolutionary history of the species (size-related traits).…”
Section: Effect Of Itv On the Variance Explained Along The Trait Spac...supporting
confidence: 68%
“…functional diversity, functional traits, intraspecific trait variability, leaf area, leaf mass per unit of the leaf area, plant strategies, trait space Editor: Roberto Salguero-Gomez trait (Siefert et al, 2015). In fact, leaf economic traits showed a higher degree of ITV compared to size-related traits, with the former determined to a greater extent by environmental filtering than by species' evolutionary history (Capdevila et al, 2023;Flores et al, 2014). Therefore, it is reasonable to hypothesise that traits that are more phylogenetically conserved, such as sizerelated traits (e.g., leaf area, Moles et al, 2005;Ávila-Lovera et al, 2023), could display fewer ITV compared to leaf economic traits and thus be more dissimilar between species than within species.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, fine-root traits may exhibit a more nuanced response that leads to less trait differentiation among species, as previously shown at the family level ( Carmona et al., 2021 ; Bueno et al., 2023 ). In contrast, aboveground traits may be subject to stronger evolutionary constraints, leading to more pronounced differences among species and families ( Carmona et al., 2021 ; Tumber-Dávila et al., 2022 ; Capdevila et al., 2023 ). Finally, the significant contribution of within-species variability that we found when combining fine-root traits might imply a wider belowground niche of a species due to differences among its individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolome thus encompasses the biochemical mechanisms through which evolutionary and ecological processes shape plant form and function (i.e., morphology and physiology ( 7 )) ( 8, 9 ). Plant form and function vary predictably among species because evolutionary and ecological processes generally act to maximize fitness ( 1014 ), thus limiting the number of morphological or physiological strategies that are viable ( 7, 15, 16 ). It follows that the metabolome should also be constrained to a limited number of strategies that maximize fitness ( 17 ).…”
Section: Main Textmentioning
confidence: 99%